Penetapan Kadar Fenolik dan Flavonoid Total Ekstrak Metanol Buah dan Daun Patikala (Etlingera elatior (Jack) R.M.SM) - Ahmad, Aktsar Roskiana; Juwita, Juwita; Ratulangi, Siti Afrianty Daniya (Pharmaceutical Sciences and Research, 2015)
Fruit and leaves of patikala (Etlingera elatior (Jack) R.M.Sm), is a traditional medicinal plants used by people to treat various diseases. The purpose of this study was to determine the total phenolic and flavonoid compounds of E. elatior fruits and leaves extracts. We extracted dried fruits and leaves samples by maceration method using methanol. Qualitative analysis of chemical compounds with certain eluent was done using Thin Layer Chromatography (TLC) to determine the group of active compounds in the extract. The amount of phenolic compounds in the sample was determined by the colorimetric method at a maximum wavelength of 744.8 nm and flavonoid at 431 nm. The results showed that the methanol extract rendemen was 1.93% for fruit and 5.17% for leaf with a total phenolic content of the fruit was 2.29 mgGAE/g b/b extract and leaf was 6.29 mgGAE/g b/b extract. And total flavonoid content of the fruit was 1.7761 % mg Quercetin/g b/b extract and leaf was 5.45 mgQE/g b/b extract.